RECONCILING INTERNATIONAL MIGRANTS’ REMITTANCES FLOW DETERMINANTS: THE CASE OF NIGERIA - O. A. Omobitan (European Scientific Journal, ESJ, 2012)
Despite the increasing importance of remittances in total international capital flows in Nigeria, the relationship between international migrants‟ remittances and its determinants remained under-researched. This study examines the determinants of international migrants‟ remittances flow to Nigeria using time series data for the period 1977-2010. The study employed the ADF and Philip-Perron modified unit root tests and based its analysis on Engle-Granger two stage long run relationships. The findings of this study strongly suggest that there exist a significant cointegration relationship between these international transfers and consumer price index, gross domestic product and openness in Nigeria. Other determinant is the US unemployment rate. More remittances inflows can be improved through official channels with the maintenance of macroeconomic and financial stability, which constitute important preconditions for the success of any policy related to remittances if inflation is kept under control. However the high proportion of remittances that goes through unofficial channels calls for urgent action to make official channel more appealing in terms of efficiency, safety, cost and anonymity.